Chemical and biological approaches for the synthesis of iron based nanoparticles - Seyedeh-Masoumeh Taghizadeh; Younes Ghasemi; Alireza Ebrahiminezhad (Shiraz University of Medical Sciences, 2017)
Iron based nanoparticles are one of the most applicable and studied nanostructures in various sciences and technologies. These nanoparticles are also introduced to the pharmaceutical and biomedical sciences due to their unique physicochemical properties such as super par magnetism, ease of synthesis, and biocompatibility. Several techniques are now developed and available for the preparation of iron based nanoparticles. Including chemical synthesis and biological synthesis which can be divided into microbial synthesis and plant mediated synthesis. Coprecipitation reaction is introduced as the main chemical method for the synthesis of magnetite nanoparticles as one of the most applied iron nanoparticle. The main approaches in biosynthesis of iron nanoparticles are also reviewed as microbial and plant mediated synthesis. In this mini review we are going to have an over view upon the main approaches for the synthesis of iron nanoparticles.